Spectroscopic Determination of pKa Constants of MADS Box Segments. Issue 5 (11th July 2012) - Řezáčová Řezáčová, Barbora Barbora; Coïc Coïc, Yves-Marie Yves-Marie; Zentz Zentz, Christian Christian; Turpin Turpin, Pierre-Yves Pierre-Yves; Štěpánek Štěpánek, Josef Josef
Abstract : We have introduced a new promising approach for the determination of pKa constants of oligopeptide intrinsic fluorophores and spectral components referring to their differently charged states. The method is based on the factor analysis of multiwavelength spectroscopic pH titration data. As an illustration, we present its application on the study of short segments of the MADS box, which is a highly conserved sequence of a so-called family of transcription factors, by techniques of UV absorption and fluorescence spectroscopies. Investigated oligopeptides contain no tryptophan but one tyrosine serving as an intrinsic fluorophore and absorber. The results indicate both good sensitivity and spectroscopic selectivity of our method, which thus may be considered as a complementary technique to conventional electrochemical methods.